Organic cation steered interfacial electron transfer within organic–inorganic perovskite solar cells. Issue 10 (20th December 2017) - Javaid, Saqib; Myung, Chang Woo; Yun, Jeonghun; Lee, Geunsik; Kim, Kwang S.
Abstract : The proton proximity arising from methylamine (MA) at TiO2 /MAPbI3 interface plays a vital role in facilitating interfacial electron transfer process Abstract : Methylammonium lead-iodide (MAPbI3, MA: CH3 –NH3 ) interfaced with rutile TiO2 is widely used in photovoltaic devices. These devices utilize the electron transfer from MAPbI3 to TiO2, which may not be explained solely by the band structures of the two bulk materials. To elucidate the interface dynamics and its impact on the electron transfer process, we have studied the interfacial features of a TiO2 /MAPbI3 system. First principles calculations and ab initio molecular dynamics simulations show that the rotational freedom of MA present within the bulk is considerably suppressed due to interaction of MA with the TiO2 substrate, highlighting orientationally ordered MA at the interface. The optimized interface structure shows the C–N axis of MA titled towards the TiO2 surface so as to maximize the interaction between N-attached H and underlying O. The very short O⋯H⋯N distance with very large hydrogen bonding energy identifies short strong hydrogen bonding (SSHB) as the origin of structural re-organization at the interface. As for the electronic structure, this proton sharing between MA and TiO2 has a critical impact on the energy level alignment at the interface, thus driving the electron transfer process from MA to TiO2 . Indeed, significant reduction in the electron transfer barrier is observed for the energetically optimal interface configuration which promotes the electron transfer across the interface and photovoltaic properties.